The Influence Of The Technology Acceptance Model On Digital Marketing Adoption Among Micro, Small, And Medium Enterprises (Msmes): The Moderating Role Of Digital Marketing Training - Ali Amzah; Marliyah Marliyah; Nurbaiti Nurbaiti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the influence of the Technology Acceptance Model on the adoption of digital marketing among MSMEs, with digital marketing training as a moderating variable. The focus of this study is on MSME participants who attended a digital marketing training program organized by the Medan City Department of Cooperatives, MSMEs, Industry, and Trade in collaboration with Lazada Indonesia. This study employs a quantitative approach, using a questionnaire distributed to 100 SME participants who attended the digital marketing training as the data collection method. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS). The results show that the Technology Acceptance Model (TAM), with its two main components—Perceived Usefulness (PU) and Perceived Ease of Use (PEOU)—has a positive and significant influence on the adoption of digital marketing. Furthermore, the digital marketing training was also found to have a positive and significant influence on the adoption of digital marketing. Furthermore, digital marketing training was found to moderate the effects of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) on digital marketing adoption. These findings suggest that SME operators who participate in digital marketing training will enhance their understanding of digital marketing, thereby encouraging them to utilize digital marketing optimally. Furthermore, understanding digital marketing concepts will certainly make it easier for SME owners to adopt digital marketing, as digital skills can expand their market reach—especially given that consumer behavior is increasingly reliant on digital platforms.